Behavior of eigenvalues in a region of broken PT symmetry - Bender, Carl M.; Klevansky, Sandra Pamela (Physical review, 2017)
PT-symmetric quantum mechanics began with a study of the Hamiltonian H=p2+x2(ix)ɛ. When ɛ≥0, the eigenvalues of this non-Hermitian Hamiltonian are discrete, real, and positive. This portion of parameter space is known as the region of unbroken PT symmetry. In the region of broken PT symmetry, ɛ<0, only a finite number of eigenvalues are real and the remaining eigenvalues appear as complex-conjugate pairs. The region of unbroken PT symmetry has been studied but the region of broken PT symmetry has thus far been unexplored. This paper presents a detailed numerical and analytical examination of the behavior of the eigenvalues for −4<ɛ<0. In particular, it reports the discovery of an infinite-order exceptional point at ɛ=−1, a transition from a discrete spectrum to a partially continuous spectrum at ɛ=−2, a transition at the Coulomb value ɛ=−3, and the behavior of the eigenvalues as ɛ approaches the conformal limit ɛ=−4.
Gesehen am 10.12.2020